2001
DOI: 10.1203/00006450-200107000-00009
|View full text |Cite
|
Sign up to set email alerts
|

Alveolar Recruitment Promotes Homogeneous Surfactant Distribution in a Piglet Model of Lung Injury

Abstract: Uneven distribution of exogenous surfactant contributes to a poor clinical response in animal models of respiratory distress syndrome. Alveolar recruitment at the time of surfactant administration may lead to more homogeneous distribution within the lungs and result in a superior clinical response. To investigate the effects of three different volume recruitment maneuvers on gas exchange, lung function, and homogeneity of surfactant distribution, we studied 35 newborn piglets made surfactant deficient by repea… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
31
0
2

Year Published

2002
2002
2022
2022

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 45 publications
(36 citation statements)
references
References 45 publications
(37 reference statements)
3
31
0
2
Order By: Relevance
“…21,22 Our protocol did not include the routine use of these maneuvers before surfactant administration. During the monitoring process, we did not record the time intervals between patient deterioration and changes in ventilator settings and/or initiation of bagging.…”
Section: Discussionmentioning
confidence: 99%
“…21,22 Our protocol did not include the routine use of these maneuvers before surfactant administration. During the monitoring process, we did not record the time intervals between patient deterioration and changes in ventilator settings and/or initiation of bagging.…”
Section: Discussionmentioning
confidence: 99%
“…This model has been studied in several mammalian species, and the response to instilled active exogenous surfactant has been consistently positive. 22,39,[128][129][130][131][132][133][134][135][136][137] However, lung lavage primarily induces surfactant deficiency resembling RDS rather than ALI/ARDS, although superimposed injury from in vivo lavage and mechanical ventilation is also present. Other animal models of direct pulmonary ALI/ARDS have also responded favorably to active exogenous surfactant.…”
Section: Animal Studies Of Surfactantmentioning
confidence: 99%
“…Using an alveolar recruitment maneuver (eg, manual bagging or a larger tidal volume) during instillation may facilitate surfactant distribution and reduce the degree or duration of hypoxia and hypotension. Studies by Krause et al 136,137 in young rabbits and piglets with lung injury induced by in vivo lavage found that several methods of volume recruitment (increased ventilator peak inspiratory pressure, tidal volume, and/or PEEP) at the time of instillation significantly improved the pulmonary efficacy of surfactant therapy.…”
Section: Animal Studies Of Surfactantmentioning
confidence: 99%
See 1 more Smart Citation
“…In addition to the pool size, positive end expiratory pressure improves pulmonary distribution and augments the surface tension-lowering effects of surfactant [5,6,7]. …”
Section: Surfactant Dosing and Redosingmentioning
confidence: 99%